Zhodnocení finanční situace podniku a návrhy na její zlepšení - Ráčil, Vojtěch (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Tato diplomová práce se věnuje tématu zhodnocení finanční situace u vybrané společnosti. Na základě teoretických poznatků bude vypracována analýza současného stavu pomocí analýzy finanční a strategické. Analýza současného stavu bude vycházet z dat za období v letech 2015 až 2019. Výsledky analýz slouží k vypracování návrhových řešení zlepšující finanční situaci podniku.

This diploma thesis deals with assessing the financial situation of a selected company. Based on the theoretical background, an analysis of the current situation will be conducted while using tools of financial and strategic analyses. The analysis of the current situation will be based on data for the period from 2015 to 2019. The results of the analysis are used to develop proposals to improve the company's financial situation.
Evaluation of the Financial Situation of a Company and Proposals for Improvements
Keywords: finanční analýza; finanční ukazatele; ekonomická přidaná hodnota; strategická analýza; SLEPTE analýza; Porterův model pěti konkurenčních sil; McKinseyův 7S model; SWOT analýza; financial analysis; financial ratios; economic value added; strategic analysis; SLEPTE analysis; Porter´s five competitive forces model; McKinsey 7S model; SWOT analysis